Editorial [Hot Topic: G Protein-Coupled Receptor Drug Targets (Executive Editors: P.M. Sexton and A. Christopoulos)] - Sexton, Patrick M.; Christopoulos, Arthur (Current Pharmaceutical Design, 2006)
G protein-coupled receptors (GPCRs) represent the largest known single gene family in the human genome. This superfamily of cell-surface proteins also constitutes the major target for approximately half the medicines on the market today. This issue of Current Pharmaceutical Design focuses on different aspects of the biology and the study of these receptors, with a broad emphasis on how these studies are influencing the modern drug discovery process. In her article, Evi Kostenis [2] presents an overview of functional assay systems for GPCRs that take advantage of the best-known signal transduction system associated with these receptors, namely, that of the G proteins themselves. The ability to translate ligand dependent and independent modulation of GPCRs into a measurable functional response in a manner that is as portable across GPCR systems as possible remains an important priority, and challenge, to GPCR-based drug discovery. The article describes how the manipulation of G protein alpha subunits, in particular, has been used to address this issue with respect to high throughput screening of GPCRs. Ethan Burstein and colleagues [3] focus on the emergence of chemical genomics, which combines genomic information, combinatorial chemistry and functional high throughput screening to accelerate drug discovery. In particular, the utility of functional assay platforms that allow a common screening approach against the widest possible array of genomic targets are discussed. The role of GPCR constitutive activity, intracellular signalling promiscuity, and G protein independent signaling are discussed within the context of general strategies for creating homogeneous assay platforms. Jen Estall and Daniel Drucker [4] focus on a specific subset of GPCRs, those targeted by glucagon and glucagonlike peptides, and discuss the potential of these receptors as drug targets. These receptors play essential roles in energy intake, absorption and disposal, and are currently hot targets with respect to diabetes, the regulation of food intake and related metabolic conditions both in the central nervous system and the periphery. The current state of knowledge with respect to selective agonists and antagonists, as well as specific aspects of the regulation of this system, are discussed. In their article, Spiro Pavlopoulos and colleagues [5] focus on another specific GPCR family that has also emerged as a very promising therapeutic target in recent years, namely the cannabinoid CB1 and CB2 receptors. Although there has been anectodal evidence for medicinal properties of cannabis and cannabis-related compounds for centuries, it is only in the modern molecular era that significant attempts have been made to delineate the biology of the receptors for these compounds and to design compounds that maintain therapeutic efficacy while minimizing and/or eliminating unwanted psychoactive effects. The discovery of endogenous cannabinoid compounds has greatly facilitated this process, and the article focuses on essential pharmacophoric elements that can be used to lead to selective signalling at cannabinoid receptors. Lei Shi and Jonathan Javitch [6] turn their attention to the area of informatics as applied to the study of GPCRs. Specifically, they highlight the key role for informatic approaches utilizing sequence information, mutagenesis data and the vast published literature to facilitate studies of GPCRs in the current climate characterized by a dearth of atomic resolution models. General approaches for integrating the vast amounts of information already available in databases and the literature, and the application to structure-funciton studies of GPCRs, are presented. Bryan Roth and Wesley Kroeze [7] draw attention to the wealth of therapeutic targets potentially available in the